Performance of bituminous mix design by using hydrated lime and shredded tyre as additive / Rosger @ Mohd Sharyl Nazman Jaudin - Jaudin, Rosger @ Mohd Sharyl Nazman (2007)
Increasing traffic volumes, heavier loads and poor performance of bituminous mixtures under adverse environmental conditions have led to the increase use and development of modified bituminous binders and asphalt mixtures. The types of modifiers that have been used include sulphur, rubbers hydrated limes, thermoplastic polymers and other additive fillers and binders is one of the best ways to overcome the problem. The problem due to pavement distress in the flexible pavement is one of the solutions which is to prevent the paving problem rather than curing it which will cost a lot of money. By preventing and also building a high strength, durable and high resistance of pavement design through its mixture design. We will be able to safe money and also the stability of the roadways. Thus, we will be able to exist safety condition to the pavement with lesser maintenance and problems.